PESAN DAKWAH HASAN AL-BANNA DALAM BUKU MAJMUA’AT AL-RASAIL - Muhammad Hanif Fuadi (Jurnal Bimbingan Penyuluhan Islam, 2020)
This article analyzes the massage of Hasan Al-Banna preaching in the book Majmu’at al-Rasail relating to the aqeedah, sharia, and morals, the study uses critical discourse analysis method of Norman Fairclough with an emphasis on the background of sosial situation until the massage of da’wah was formulated. The result of the reaserch show that the massage of da’wah in the book Majmu’at al-Rasail can be explained, among other: the massage of the faith in theological discourse, the massage of sharia in the discourse of power and the moral massage in the discourse of social relations. The monotheistic belief system must be able to provide the divine spirit in all dimensions of life. The spirit grow out of true, pure, clean faith from the element of shirk to God; the sharia system requires applicable law according to the teaching of Islam, focusing on a number of social and political problems that it the country of Egypt after the destruction of the Ottoman Caliph wich fell into British hands. The massage of Hasan al-Banna’s preaching was oriented toward reforming the living system wich was damaged by colonialism and desirous of returning it to the Islamic system.